Odpowiedzi

2010-01-06T15:31:43+01:00
3a + b = 27
a / b = 3 / 2

3a + b = 27
3a=2b

b=27-3a
3a=2(27-3a)
3a=54-6a
9a=54
a=6

3a=2b |:2
b=3a/2
b=9

Mam nadzieję, że pomogłam i liczę na naj;))
2 3 2
Najlepsza Odpowiedź!
2010-01-06T15:31:48+01:00
3a + b = 27
a/b = 3/2 dla b≠0

b = 27-3a
3b =2a

3(27-3a)=2a
81-9a=2a
81=11a /:11
a=⁸¹/₁₁

b = 27-3a
b = 27-3*⁸¹/₁₁
b=27- ²⁴³/₁₁
b=²⁹⁷/₁₁ - ²⁴³/₁₁
b=⁵⁴/₁₁

-----------------------------------------------------------------

3a + b = 27
b/a = 3/2 dla a≠0

b = 27-3a
3a =2b

3a=2(27-3a)
3a=54-6a
9a=54 /:9
a=6

b = 27-3a
b = 27-3*6
b = 27-18
b=9